Starlink dan Tantangan Kedaulatan Ruang Udara Digital Indonesia dalam Perspektif Hukum Udara dan Hukum Angkasa - Hafizah Nurul Izzati; Ashar Fawazy; Raihan Maulana Gibran (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The development of Low Earth Orbit (LEO) satellite systems such as Starlink has transformed global internet services while challenging state sovereignty, particularly in Indonesia’s airspace and digital domain. This study analyzes the implications of Starlink on digital airspace sovereignty from the perspectives of air law and space law, as well as existing legal frameworks and possible solutions. Using a normative juridical method with statutory, conceptual, and comparative approaches, the findings reveal that the absence of a clear boundary between airspace and outer space creates jurisdictional ambiguity and weakens state control over cross-border data flows. In addition, the dominance of private actors in orbital and frequency control risks inequality for developing countries. Therefore, sovereignty must be reconstructed as a multidimensional concept, supported by adaptive legal reforms at both national and international levels.